Primary Anti-Phospholipid Antibody Syndrome: Real-World Defining Features of Rethrombosis in the Course of Disease. (10th November 2022) - Moraes-Fontes, Maria Francisca; Pedro, Filipa; Campos, Maria Manuel; Fernandes, Melissa; Yavuz, Sule; Oliveira, Francisco; Panarra, António
Abstract : Objective . We aimed to identify features that allow differentiation of primary antiphospholipid syndrome (PAPS) patients that suffer recurrent thrombotic events (RTE) despite anticoagulation, from the other diagnosed PAPS patients. Methods . This was an exploratory study of anticoagulated PAPS patients attending an Autoimmune Diseases Unit (1998-2018). From 2016, anti-phospholipid antibodies and lupus anticoagulant were determined for each patient at consecutive visits, collected together with retrospective clinical characteristics, laboratory, and therapeutic markers and compared according to the occurrence of thrombotic events during follow-up. Results . Overall, two thirds of the patients were female, 93% were Caucasian, with a median age of 40 years at diagnosis, for a median time of 11.5 years in follow-up. Out of 54 patients, 10 were identified with RTE. There were no significant differences among the RTE and non-RTE patients as far as classical risk factors for clotting disorders. The RTE group was characterized by a higher proportion of younger patients, male sex and positivity for all laboratory markers, and initially and over follow-up as well as a sustained high-risk profile based on APS laboratory markers. Anticardiolipin IgG at onset was the only statistically significant marker of the RTE group. At the end of follow-up, consistent reversion to negative status was a rare event, observed in 20% of RTE vs. 25% of non-RTE patients. Conclusions . Despite therapy, we were able to identify features associated to thrombotic events in patients with PAPS. Prospectively regular clinical and laboratory monitoring might be warranted in order to treat APS more assertively.